Assessment of the knowledge of health professionals about preventive pharmacotherapy for COVID-19 (Research, Society and Development, 2022)
Since its emergence in 2019, SARS-CoV-2 has proved to be very versatile and lethal. The numbers of deaths and hospitalizations have become a problem, therefore, it is necessary to find a measure against the infection. Therefore, new studies have emerged from existing drugs, such as Hydroxychloroquine, Nitazoxanide, Azithromycin and Ivermectin. However, amidst the uncertainties, the use of these drugs was widespread, even after carrying out studies that did not find the real benefit of this therapy, becoming a problem, especially in Brazil. Therefore, the present study sought to understand the perspective of health professionals, from an electronic form, in relation to early treatment as well as preventive measures for COVID-19. Regarding early treatment, most individuals (69/88) do not believe in the use of drugs as a prophylactic or cure, and those over 39 years of age had higher confidence levels (40% and 28%) in this pharmacological management in relation to professionals aged between 18 and 39 years (14.3% and 1.6%). When asked about the safety and efficacy of vaccines, professionals with a technical level had a lower confidence index (82.4%) when compared to those with a higher level (97.2%). The data indicate that health professionals tend to seek updates on COVID-19, but that specific groups should receive attention, aiming to combat misinformation and fully implement the concept of evidence-based health.